Endogenous derivation of the optimal policy measures to improve the water quality in Barada Basin, Syria - Yoshiro Higano; Rimah Melhem (European Regional Science Association (ERSA), 2002)
Barada Basin, where the capital of Syria, Damascus, is located, in hence where most of the human activities are concentrated, suffers from serious environmental problems due to urbanization, industrialization, and overexploitation of environmental media. Huge amounts of wastewater (domestic, industrial, and agricultural) are discharged everyday to the land, Barada and Awaj Rivers without sufficient treatment converting the only-two water bodies in the region to waste dump. In this paper, an optimal policy will be introduced including set of policy measures to improve the water quality in the rivers by running a mathematical model and simulating the data available.
Keywords: 330